Report on industrial attachment with YTL PowerSeraya Pte Limited - Wong, Ci Siang (2014)
This report contains and presents the industrial attachment experience gained by the author in the 22-week industrial attachment at Pulau Seraya Power Station. Throughout this period, the author was attached to the Electrical Maintenance department under Utilities Group. The primary aim of the attachment is to get exposed to the engineering practices through assisting and involvement in the department projects. In particular, the report discusses the plant operations and implementation of protection relay replacement and revision of generator RSO test projects, both in literature review and implementation. Besides that, numerous minute yet critical tasks assigned to the author contributed to the successful implementation of the projects. The problems and challenges overcome are depicted inside the report. Lastly, the report covers the experience involved in reinforcing power engineering concepts, developing soft and hard skills, while making contributions to the company. Generally, the internship has provided the author with basic technical skills and other essential working skills to prepare for life as an engineer in the future